SISTEM PENDIDIKAN PONDOK PESANTREN DALAM MEMBENTUK KEPRIBADIAN MULIA SANTRI PUTRA DI PP. AL FATTAH 1 SIMAN - Saifuddin; Zuhri, Mohammad (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2020)
The Islamic boarding school education pattern is very relevant if it is related to education in order to shape personality. Because learning in Islamic boarding schools is closely related to ethics, morals and 24 hour learning which always teaches the role models of the ulama ’as an inseparable part of the Islamic boarding school. The purpose of this study was to determine: (1) the education system of the Al Fattah Islamic boarding school. (2) the efforts made in shaping the personality of the students (3) the supporting and inhibiting factors of the Islamic boarding school education system in shaping the personality of the students. From the research results, it was concluded that the applicable education system in PP. Al Fattah covers management, objectives, curriculum and teaching and learning processes. Efforts made by education providers in shaping personality are by personal approach, good habituation, application of discipline, exemplary, learning about noble morals, planting personal awareness and giving sanctions. The factors that support the application of the education system in shaping the personality of the students are wise caregivers, competent masyayikh and assatidz, firm administrators, consistent regulations, supportive means. While the inhibiting factors are the students have not been able to manage the time, the lack of awareness of the students and a feeling of laziness in the students.